2021
DOI: 10.1007/s40171-021-00272-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Big Data and Artificial Intelligence on Industry: Developing a Workforce Roadmap for a Data Driven Economy

Abstract: Big Data and Artificial Intelligence (BD&AI) have become so pervasive, and the opportunities they present so transformative, that they are viewed as essential for competitive growth. Since the number of firms adopting BD&AI technologies is growing exponentially, the demand for BD&AI practitioners is also growing at a rapid rate. However, several studies indicate that there is a BD&AI talent shortage and skills gap between labor market requirements and expertise available in the current workforce. This talent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 56 publications
0
27
0
1
Order By: Relevance
“…Governments may provide their workforce with a competitive advantage by educating, developing, and enabling access to people with sophisticated computer and analytics skills. Because AI education necessitates hands-on experience, industry and academia should work together to develop apprenticeship programs that allow students to rotate around multiple firms and learn about AI applications in a variety of sectors and job functions (Johnson et al 2021). Employers must be able to share their expertise with students through academia.…”
Section: Shortage Of Ai-skilled Workersmentioning
confidence: 99%
“…Governments may provide their workforce with a competitive advantage by educating, developing, and enabling access to people with sophisticated computer and analytics skills. Because AI education necessitates hands-on experience, industry and academia should work together to develop apprenticeship programs that allow students to rotate around multiple firms and learn about AI applications in a variety of sectors and job functions (Johnson et al 2021). Employers must be able to share their expertise with students through academia.…”
Section: Shortage Of Ai-skilled Workersmentioning
confidence: 99%
“…This paper builds on research that we conducted as members of the New Jersey Big Data Alliance during December 2018 and January 2019 to develop a "New Jersey Big Data Workforce Roadmap" that could ensure a skilled workforce in the State of New Jersey is prepared for current and future technological changes (Johnson et al 2021). In this research, we examined specific technological changes, such as AI, machine learning, and large-scale automation, that are impacting New Jersey's major industry clusters (e.g., health care, logistics, food, financial services, clean energy, and advanced manufacturing), and the resultant skills needed for a competitive workforce.…”
Section: Background To the Researchmentioning
confidence: 99%
“…Our research concluded, "most companies have not realized the full potential of these technological advances due to a number of barriers, including talent shortages. By educating, training, and facilitating access to individuals with advanced computing and analytics skill sets, New Jersey can provide a competitive advantage for its employers" (Johnson et al 2021). However, training in business ethics and applying ethical considerations through critical thinking skills was not a part of that research.…”
Section: Background To the Researchmentioning
confidence: 99%
“…Further implementation of technologies based on deep learning, machine learning, and other types of artificial intelligence will not necessarily eliminate existing jobs in their entirety. While some of the simpler jobs that do not require significant intellectual effort, empathy, or intuition may disappear, and new jobs related to the emerging technologies will eventually appear [20][21][22], the main tendency of the following years will be the redesign of existing jobs to accommodate technological advances.…”
Section: Micro-organizational Variables Job Variety and Job Richnessmentioning
confidence: 99%
“…Although several attempts were made to understand the nature of the interrelationship between AI-related technologies and the structural characteristics of an organization [20][21][22]30,39,40,46], to our knowledge, this study represents the first in its kind addressing the issue systemically across multiple dimensions of the ideal-type of a typical organizational structure. Indeed, the previous studies were mainly concerned with micro job-related issues, both vertically [20][21][22][23]25,26] and horizontally [29,31,32]. The important mesolevel variables-mainly related to the span of control, number of hierarchical levels, centralization, standardization, formalization, and incentives-have been consistently neglected by scholars.…”
Section: Main Findingsmentioning
confidence: 99%